INFORMATION AND MEDIA COMPETENCE: CONTENT AND STRUCTURE - Toyirova Rayxona Ismatjon kizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: In the contemporary digital era, information and media competence has become one of the most essential competencies for learners, teachers, and professionals. Rapid technological development, the expansion of digital communication, and the increasing influence of social media platforms have significantly transformed the ways individuals access, analyze, evaluate, create, and disseminate information. Consequently, educational systems around the world are increasingly focusing on developing information and media competence as an integral component of lifelong learning and professional development. This article examines the concept, content, and structural components of information and media competence from theoretical and practical perspectives. The study analyzes major international frameworks and scholarly approaches related to information literacy, media literacy, digital literacy, and critical thinking. Particular attention is paid to the interrelationship between information competence and media competence, emphasizing their role in fostering analytical thinking, responsible communication, ethical behavior, and digital citizenship. The article also discusses the pedagogical significance of integrating information and media competence into educational curricula, especially in higher education and foreign language teaching. Furthermore, the paper highlights the importance of developing students’ abilities to critically evaluate media messages, identify misinformation, use digital technologies effectively, and participate responsibly in the global information environment. The findings demonstrate that information and media competence is a multidimensional construct consisting of cognitive, technological, communicative, ethical, and critical components that collectively support effective learning and professional success in the twenty-first century.